BMP9 induces postnatal zonal stratification of immature articular cartilage through reconfiguration of the existing collagen framework - Anderson-Watters, Miles; Khan, Ilyas M. (Frontiers in Cell and Developmental Biology, 2025)
Articular cartilage lines bones in synovial joints, and its main structural element, collagen, has an arcade-like arrangement formed from an initially random network in a process called postnatal maturation. This reshaping of the extracellular matrix is similar across all species and is critical for the lifelong strength and durability of cartilage. Collagen remodelling during maturation is difficult to study because it spans a period of time between birth and puberty, and in larger animals this can be months or years. In this study, we show that growth factor bone morphogenetic protein-9 (BMP9) induces collagen remodelling in intact immature articular cartilage explants within 21 days, generating the characteristic arcade-like structure and zonal anisotropic architecture of adult cartilage. In explants exposed to BMP9, collagen fibrils underwent angular displacement from 19° to 78° with respect to the surface, cell density decreased 1.77-fold, and chondrons were significantly larger. The absence of labelling with anti-COL2¾m, a marker of collagen turnover, showed that the existing fibril network was restructured. We found that stromelysin-1 (metalloproteinase-3, MMP3) gene expression was consistently upregulated, whilst other MMP transcript levels were unchanged or reduced. Remodelling was dependent on proteoglycan turnover and could be inhibited using PD166973. These data suggest a possible mechanism whereby MMP3 induces proteoglycan turnover and depolymerises collagen fibrils enabling them to undergo spatial reorganisation. This process may be driven by tissue swelling, which generates directional strain to align fibrils into an arcade-like pattern. The ability to induce tissue maturation advances the potential for engineering durable and functional cartilage for patients requiring joint repair due to diseases such as osteoarthritis.